Studi Perubahan Luasan Vegetasi Mangrove Mengunakan Citra Landsat Tm Dan Landsat 7 Etm+ Tahun 1998 – 2010 Di Pesisir Kabupaten Mimika Papua - Fajri, Fajri; Subardjo, Petrus; Pribadi, Rudhi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangrove ecosystem is one of kind forest that naturally influenced by tides. Mangrove root’s system have capability to hold and capture sediment transported by waves or currents which bring to sedimentation or soil formation arise and become the new land for mangrove vegetation. Tailings from the mining PT. Freeport Indonesia in Tembagapura cusher form of a smooth stone is passed through Aghawagon River, followed Otomona River and deposited in the Regional Deposition Ajkwa (DPA), the possibility of 5-10% of particles remaining Sand Mining (tailings) carried out the most subtle to the Estuary Ajkwa and the Arafura Sea (PT Freeport Indonesia, 1999). Sedimentation due to the flow of the remaining mine sand from the river and taken apart Ajkwa currents, thought to affect an area of mangrove forests that exist around the estuaries in the coastal Mimika. Aim of this study is determining the extent of vegetation change in Mimika coastal mangrove District, Papua during 1998 to 2010 using multitemporal satellite imagery. The study was conducted in November 2010 to May 2011 using 1998’s Landsat TM imagery, Landsat 7 ETM + in 2002, Landsat 7 ETM + in 2006, and Landsat 7 ETM+ 2010, by using descriptive method. The results of this study indicate changes in the extent of mangrove vegetation of the estuary area to Mawati Kamora is varied, ie, in the year 1998 to 2002 has improvement 250.64 ha and 234.91 ha of reduction, in the year 2002 to 2006 has improvement 131.82 ha and 193.37 ha of reduction, in the year 20006 to 2010 experienced a reduction of 175.94 ha and 89.28 ha. Supply of sediment input in the form of tailings or suspected influence on the addition of mangrove vegetation in the Mimika District coastal area of Papua, particularly in the area and Kamora Ajkwa River Estuary, while the reduction of mangrove vegetation in the Coastal area of Timika, Papua, probably caused from to hydrological factors of the currents and waves.